Sport policy and the integration of refugee backgrounded women - Hayley Truskewycz; Ruth Jeanes; Justen O'Connor (Bern Open Publishing, 2024)
Introduction Sport is regularly used as a policy-led tool to facilitate outcomes aligned with resettlement and integration of refugees. However, the understanding of the role of sport in the resettlement of refugees is limited by a narrow focus on policy-led integration outcomes and player participation (Nunn et al., 2021). Moreover, refugee men prevail as the dominant participants, in not only sporting programs, but also within the research that informs the sport resettlement agenda (Ekholm et al., 2019). Therefore, the participation of refugee women in sport policy and programming is largely understood through refugee men's experiences, where the role of sport in resettlement and the daily lives of refugee women is less well understood. This research, guided by postcolonial feminism, examined how sport is deployed as a resettlement and integration policy tool for refugee backgrounded women living in Melbourne, Australia, and aimed to determine the relevance of sport in the lives of refugee backgrounded women. Methods Bacchi (2009) framework for policy analysis examined three government sport policies texts that represented refugee integration as a 'problem' to be managed through sport. Interviews with policy actors and sport program providers investigated practices and discourses underpinning refugee women's inclusion in sport programming. Ethnographic fieldwork conducted over a 12-month period with a culturally diverse community football club, explored the role of sport in the lives of refugee backgrounded mothers and their children. Data was analysed using critical discourse analysis and thematic analysis. Results Factors at policy level, i.e. the tokenistic presence of women and girls in policy texts, and programming level, i.e. their inclusion into male dominated spaces shaped by neoliberal agendas, continue to resist refugee women's participation in mainstream sport. Refugee women's secondary presence in policy and programming was reinforced by temporary, sporadic and competitive funding opportunities that were heavily reliant on participation numbers and hegemonic masculinity, preserving the privilege of the status-quo. Integration in the policy texts was understood as belonging to the dominant Anglo-Australian culture, but belonging was contested, and the refugee mothers in this study understood belonging as being to their own cultures. Their sporting club was a space of belonging, stress relief, social connection, agency and cultural maintenance. The sport club was an important part of their lives as individuals, and was an important aspect of parenting and motherhood. Discussion/Conclusion Our study indicates that policy level and policy actors that promote the inclusion and integration of refugees through sport regularly marginalise refugee women and place them as tokenistic participants. Our findings suggest that ethno-specific, community driven sporting spaces are not oppositional, but play a complementary role in policy-led integration agendas. Sport can play an important role in resettlement among refugee backgrounded mothers and their families, where it offers a stable foundation from which other outcomes and benefits are able to facilitated. If sport has the capacity to facilitate positive social outcomes in line with settlement and integration, then greater efforts must be made to ensure women and girls are included and represented in the sport rhetoric (Ekholm et al., 2019). References Bacchi, C. (2009). Analysing Policy: What's the problem represented to be? Pearson. Ekholm, D., Dahlstedt, M., & Rönnbäck, J. (2019). Problematizing the absent girl: Sport as a means of emancipation and social inclusion. Sport in Society, 22(6), 1043-1061. https://doi.org/10.1080/17430437.2018.1505870 Nunn, C., Spaaij, R., & Luguetti, C. (2021). Beyond integration: Football as a mobile, transnational sphere of belonging for refugee-background young people. Leisure Studies, 41(1), 42-55. https://doi.org/10.1080/02614367.2021.1962393